Error Analysis on Voicing Sounds Uttered by English Department Students at State Islamic Institute of Madura - Abdul Wafi; Rinta Ratnawati; Ansharul Fuqaha' (Institut Agama Islam Negeri Madura, 2020)
English pronunciation is unique and said as badly spelled. The difference between what has been written with what they should pronounce is a vital factor. This study is aimed at finding out the error in pronouncing the voiced and voiceless sounds made by the students of Tadris Bahasa Inggris IAIN Madura. The study uses a descriptive design with qualitative data. The population is second-semester students who are taking pronunciation subject in C class with 32 students. The result shows that of 10 minimal pairs tested to the students, the percentage students who can pronounce the words correctly is that 37% students for 1st minimal pairs, 81% for 2nd one, 31% for 3rd one, 50% for 4th one, for 5th one 31% in the word 'laugh' and 87% in the word 'love', 21% for 6th one, for the 7th one 6% in the word 'measure' and 18% in the word 'sure', for the 8th one 9% in the word 'stronger' and 84% in the word 'stranger', for the 9th one 21% in the word 'eyes' and 93% in the word 'rats' and 31% in the word 'buses', for the 10th one 31% in the word 'robbed' and 31% in the word 'washed' and 12% in the word 'needed'. It can be concluded that most of the students are not aware of voicing sounds in English pronunciation. It is suggested that giving drill of minimal pairs and introducing them to places and manners of articulation might be able to improve their awareness to produce correct pronunciation.